Influence of infused cell dose and HLA match on engraftment after double-unit cord blood allografts - Avery, Sharon (American Society of Hematology, 2011)
The influence of cell dose and human leukocyte antigen (HLA) match on double-unit cord blood (CB) engraftment is not established. Therefore, we analyzed the impact of cell dose and high-resolution HLA match on neutrophil engraftment in 84 double-unit CB transplant recipients. The 94% sustained engraftment rate was accounted for by 1 unit in nearly all patients. Higher CD3(+) cell doses (P = .04) and percentage of CD34(+) cell viability (P = .008) were associated with unit dominance. After myeloablative conditioning, higher dominant unit total nucleated cell (TNC), CD34(+) cell, and colony-forming unit doses were associated with higher sustained engraftment and faster neutrophil recovery (P = .07, P = .0008, and P < .0001, respectively). Total infused TNC (P = .0007) and CD3(+) cell doses (P = .001) also significantly influenced engraftment. At high-resolution extensive donor-recipient HLA disparity was frequent, but had no influence on engraftment (P = .66), or unit dominance (P = .13). Although the unit-unit HLA match also did not affect sustained engraftment (P = 1.0), recipients of units closely (7-10 to 10-10) HLA-matched to each other were more likely to demonstrate initial engraftment of both units (P < .0001). Our findings have important implications for unit selection and provide further insight into double-unit biology.